2021
DOI: 10.1007/s00359-021-01524-z
|View full text |Cite
|
Sign up to set email alerts
|

Optocollic responses in adult barn owls (Tyto furcata)

Abstract: Barn owls, like primates, have frontally oriented eyes, which allow for a large binocular overlap. While owls have similar binocular vision and visual-search strategies as primates, it is less clear whether reflexive visual behavior also resembles that of primates or is more similar to that of closer related, but lateral-eyed bird species. Test cases are visual responses driven by wide-field movement: the optokinetic, optocollic, and optomotor responses, mediated by eye, head and body movements, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 61 publications
(90 reference statements)
5
20
0
Order By: Relevance
“…As in the adult study (Wagner et al 2021), most of our data did not show normal distributions (data not shown). Therefore, we used nonparametric statistics, speci cally the Mann-Whitney U test to analyze the relation of unpaired samples.…”
Section: Statisticssupporting
confidence: 49%
See 4 more Smart Citations
“…As in the adult study (Wagner et al 2021), most of our data did not show normal distributions (data not shown). Therefore, we used nonparametric statistics, speci cally the Mann-Whitney U test to analyze the relation of unpaired samples.…”
Section: Statisticssupporting
confidence: 49%
“…In some cases, we also use the term " rst day of response", meaning the rst PHD at which quantitative data were recorded and the owls responded to the visual stimulus. Optocollic reactions were automatically analyzed with a temporal resolution of 80 msec (for details see Wagner et al 2021). The azimuthal orientation of the owl's head and the azimuthal position of the pattern were synchronously derived and stored for further processing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations